Integration of a heuristic approach and information-communicative technologies as the basis of improvement of the university educational process - Morozova, Natalia I. (Journal of the Belarusian State University. Journalism, 2020)
The discusses the application ofinformation and communication technologies in the educational process in institutions of higher education. Two main directions of the application of information and communication technologies in modern higher education are characterised. Existing approaches to informatisation of domestic education are discussed. It substantiates the position that information and communication technologies expand the possibilities of the educational environment and create the basis for obtaining qualitatively new results both in teaching and in the development of students’ personalities. As an example,the features of the use of information and communication technologies at the Belarusian State University are presented, in which the educational process involves the active use of electronic learning tools by both students and teachers and is based on the principles of creative online education.
Keywords: distance learning; distance form of part-time education; information and communication technology; electronic learning tools; educational process; heuristic training